A new numerical technique for local fractional diffusion equation in fractal heat transfer - Yang, Xiao-Jun (2017)
In this paper, a new numerical approach, embedding the differential transform (DT) and Laplace trans- form (LT), is frstly proposed. It is considered in the local fractional derivative operator for obtaining the non-differential solution for diffusion equation in fractal heat transfer.